Fungsi Organizing Kepala Desa Dalam Pengelolaan Badan Usaha Milik Desa (Bumdes) di Desa Aliantan Kabupaten Rokan Hulu - Marhamah, Siti; Syafrizal, Syafrizal (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
This study aims to determine the organizing function of village heads in the management of village-owned enterprises (BUMDes) in Aliantan Village, Kab. Upstream. The research method used in this study is a descriptive method with qualitative data analysis, the data obtained through data collection is then interpreted according to the research objectives that have been formulated and obtained through interviews. Based on the results of the research that the authors have done, it shows that the Village Head's Organizing Function in the Management of Village-Owned Enterprises (BUMDes) in Aliantan Village, Kab. Rokan Hulu has been running according to its functions but the management implementation is still not optimal, this is due to a lack of adequate human resources.